Glucose to Complications: Understanding Secondary Effects in Diabetes Mellitus - P. K. Prabhakar (Talenta Publisher, 2024)
Background: Diabetes Mellitus (DM) is a complex metabolic disorder characterized by persistent hyperglycemia, impacting millions globally. While glucose control is central to its management, understanding secondary complications is crucial for comprehensive care. Objective: This paper explores the intricate relationship